Understanding the groundwater system of a heavily drained coastal catchment and the implications for salinity management - Simpson, Trevor Baylie (Cranfield University, 2007)
The Thurne catchment in north-east Norfolk, UK, is an extremely important part of the Broads National Park, an internationally important wetland environment. Extensive engineered land drainage of the marshes of this low-lying coastal catchment over the past two centuries has led to land subsidence and the need for drainage pumps to control water levels sufficiently below sea-level to maintain agricultural productivity. Consequently, seawater from the North Sea has intruded into the underlying Pleistocene Crag (sand) aquifer and brackish groundwater enters into land drainage channels, thereby raising their salinity. Powerful pumps discharge these brackish drainage waters into a Special Area of Conservation (SAC) and RAMSAR site, leading to adverse ecological impacts on salt-sensitive species. Chloride concentrations within drainage channels throughout the network have been found to significantly vary, with several influential factors affecting channel salinity such as proximity to the sea and connectivity to the underlying aquifer. A thorough understanding of the surface-water/groundwater system and a subsequent quantification of the various processes has been necessary for the development for the drain/aquifer interactions and a numerical groundwater model. These models are used to estimate the long-term distribution of the salinity within the drainage system under current conditions. The model credibility is justified by comparable aquifer-drain water balance, a comparable coast water inflow/ total groundwater ratio and the particle tracking from the coastal reaches trace to previously-measured saline-vulnerable locations. The numerical groundwater model has demonstrated that the average daily inflow of saline groundwater into the Crag aquifer of the Thurne catchment is 3,081 m3/day, of which the HempsteadMarshes main drain is one of the main conduits for saline inflow into the Brograve system, which discharges directly into the SAC. Various changes to the engineering design or operation of the drainage system have been proposed to minimise the saline inflow to the SAC, but the implementation of any proposals must be considered in conjunction with the current dynamics of the system. Three separate management or engineering remedial measures have been modelled: (i) raising the water levels in the drains of the Hempstead Marshes in the north east of the catchment (ii) lining the main drain of the HempsteadMarshes with low permeability material, and (iii) The construction of a new coastal open ditch drain which is intended to ‘intercept’ the saline intrusion and prevent ingress into inland drains of the Brograve system. The results suggest that raising the water levels in the Hempstead Marshes will reduce the saline inflow into the Brograve sub-catchment substantially, and decrease the overall saline inflow into the Thurne catchment from 3081 m3/day to 2822 m3/day). The lining of the main drain in Hempstead produces a less than 10% decrease in saline inflow into the catchment from 3,081 m3/day to 2,958 m3/day. The simulated coastal interceptor drain could in theory through maintaining a low groundwater head near the coast, prevent the inflow of saline groundwater into the Brograve system. However, such a drain would increase the saline inflow across the coastal boundary by around six times (from 3,081 m3/day to 19,750 m3/day), remove large quantities of fresh groundwater from the Pleistocene Crag aquifer and lead to high energy and pumping costs. The research has shown that there are partial solutions to reducing the saline inflow into the drainage systems in this lowland coastal catchment. However, any intended alterations must first consider other potential impacts, such as changes to flood risk, land management restrictions or hydrodynamic effects on the receiving watercourse through changed discharge volumes.